Studies on Monstereae (Araceae) of Peninsular Malaysia I: Rhaphidophora megasperma, a New Record for West Malaysia - Baharuddin Sulaiman; Peter C. Boyce (Tropical Life Sciences Research, 2010)
Rhaphidophora megasperma Engl., a species hitherto regarded as endemic to Sarawak, East Malaysia, is published as a new record for Peninsular Malaysia. It is the first species in the Rhaphidophora Spathacea group recorded for western Sunda. The species is illustrated and a key to the perforate-laminated Rhaphidophora in Peninsular Malaysia is presented. Rhaphidophora megasperma Engl., spesies yang dianggap hanya endemik di Sarawak kini dilaporkan sebagai satu rekod baru untuk Semenanjung Malaysia. Ini merupakan spesies pertama dari kumpulan Rhaphidophora Spathacea yang direkodkan di Sunda Barat. Ilustrasi dan kekunci untuk spesies lamina-berlubang Raphidophora untuk Semenanjung Malaysia telah dipamerkan.